HUBUNGAN PENGETAHUAN ORANG TUA DENGAN KEPATUHAN PENGOBATAN PADA ANAK PENDERITA TUBERCULOSIS (TBC) DI PUSKESMAS PERAK TIMUR SURABAYA - Ethyca Sari (Bahasa Indonesia, 2020)
Tuberculosis is a disease that is transmitted through the respiratory system that can attack at any age, especially at the age of children who experience decreased immune system and close contact with people with Tuberculosis caused by Mycobacterium tuberculosis. The purpose of this study was to determine the relationship of parental knowledge with treatment adherence in children with tuberculosis. The method used in this study is to use a cross-sectional method. The population in this study was 15 with the number of samples used as research respondents was 15 respondents (parents). Sampling is done by Total Sampling. The research instrument used was a questionnaire, observation and interview. The results showed that as many as 9 respondents (60%) had a sufficient level of knowledge with compliant behavior. Analysis of data using the Spearman test and obtained a significance value (p) of 0.620 where p <0.05, which means there is no relationship between parental knowledge and medication adherence in children with tuberculosis. It can be concluded that there is no relationship between parental knowledge and treatment adherence in children with tuberculosis in Puskesmas Perak Timur Surabaya.With this research, it is expected to increase health knowledge, especially in children with tuberculosis in the Health Center in East Surabaya Surabaya by means of health education.